The interfacial compatibility between a potential CO2 separation membrane and capture solvents - Jun Gao; Yuchen Zhang; Jiyoung Son; Jason E. Bara; Kathryn E. O'Harra; Mark H. Engelhard; David J. Heldebrant; Roger Rousseau; Xiao-Ying Yu (Carbon Capture Science & Technology, 2022)
Water-lean solvents are considered as a promising solution for carbon dioxide (CO2) capture. Candidate CO2 capture molecules include N-(2-ethoxyethyl)-3-morpholinopropan-1-amine (2-EEMPA), 3-methoxy-N-(pyridine-2-ylemthyl)propan-1-amine (MPMPA), and 1-((1,3-Dimethylimidazolidin-2-ylidene)amino)propan-2-ol (1-IPADM-2-BOL). When integrating the water-lean solvents with the separation membrane to form a hybrid system, it would have a higher driving force to pull CO2 through a membrane. In addition, including a membrane in the direct air capture (DAC) system would reduce the evaporation of capture solvents. Therefore, it is important to understand the chemical compatibility of the solvents with the separation membranes to better integrate them into the process for DAC of CO2. Characteristic peaks of water-lean solvents and separation membrane were observed in the static spectral measurements of time-of-flight secondary ion mass spectrometry (ToF-SIMS). For example, m/z+ 217.190 C11H25N2O2+, m/z+ 181.129 C10H17N2O+, and m/z+ 172.145 C8H18N3O+, are the protonated 2-EEMPA, protonated MPMPA, and protonated 1-IPADM-2-BOL, respectively. Similarly, the fragment of CO2 separation membrane, m/z+ 263.082 C16H11N2O2+, a synthesized PEEK-ionene, was observed, showing molecular detection of ToF-SIMS. In addition, x-ray photoelectron spectroscopy (XPS) was performed to quantitatively verify the change of carbon ratio at the interface, indicating the interactions between water-lean solvents and the separation membrane. These findings show that the interface between the CO2 separation membrane and water-lean solvents should be studied at the molecular level, because they provide insights into how we could design hybrid systems comprised of CO2 separation membranes and capture solvents.